Pyogenic psoas muscle abscess report of three cases - Takagi, S (Hinyokika kiyo. Acta urologica Japonica, 1994)
We report three cases of primary psoas muscle abscess. Two of these cases were treated by open drainage through a lumbar incision and the other was by ultrasonography (USG)-guided percutaneous aspiration of the abscess. Antibiotic therapy was also instituted in all cases. Post-operatively, the patients recovered well with no sign of recurrence. USG-guided percutaneous drainage combined with appropriate antibiotic therapy appears to be the first choice procedure for treatment of the primary psoas abscess if correct diagnosis is promptly made and the procedure can be performed